The Effect Of Leadership Styles On Employees’ Job Commitment In An Organization - Choo, Chiew Erh (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study examines the relationship between (1) transformational leadership style, (2) transactional leadership style, and (3) laissez-faire leadership style and employees’ job commitment in an organization. The study sample consisted of 85 employees employed in an organization in Pulau Pinang. The results showed that there was a strong, positive correlation between transformational leadership style and employees’ job commitment, whereas transactional leadership style showed that there was a small, positive relationship with employees’ job commitment. Besides that, laissez-faire leadership style had an insignificant relationship with employees’ job commitment in the study context. Researcher concluded by suggesting some directions for such research.